Pelatihan Peningkatan Kualitas Pembelajaran Di Madrasah Melalui Manajemen Mutu Terpadu - Solechan Solechan; Zahrotun Ni’mah Afif; Beny Sintasari; Mar’atul Azizah; Ari Kartiko (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
This research aims to explore and analyze the impact of implementing integrated quality management (TQM) in improving the quality of learning at MTS Al Hidayah. The community service method is used as the main approach, with a focus on designing and implementing comprehensive training programs for teachers and school staff. This approach includes an initial evaluation to identify madrasah needs, designing training programs that are appropriate to the local context, as well as ongoing implementation and monitoring. The research results show that TQM training is effective in improving teacher teaching competence, encouraging the use of formative evaluation, and strengthening transformational leadership in madrasas. Ongoing evaluations show improvements in the physical infrastructure and collaborative school culture. This research contributes to the literature on the implementation of TQM in the context of madrasah education, with practical implications for the development of sustainable educational policies and strategies